A Foucauldian Discourse Analysis of the European Union’s Anti-Bullying Policies - Ghorbanpour, Fateme (My University, 2025)
Bullying is a serious problem among school children with devastating short-term and long-term effects on their well-being. Despite the existence of extensive research and anti-bullying policies, bullying is still a prevalent issue worldwide, including Europe. This master’s thesis focuses on examining how the problem of bullying is constructed within anti-bullying policies and how solutions are being framed. The aims of this research are met through analyzing recent anti-bullying policies published by the European Union body. The analysis is carried out through a Foucauldian Discourse analysis. This research reveals several key findings regarding problem construction, solution framing, and dominant discourse around bullying: School bullying is framed as a challenge to health and well-being, a challenge to academic success, an individual problem, and a challenge to equality. The recommended solutions to the problem include cooperating with other experts, implementing school-based programs (including anti-bullying programs), and providing system support. The findings reflect the dominance of psychological and neoliberal discourse around bullying. By promoting these dominant discourses in the majority of bullying research, they fail to address more systemic grounds that can be the main cause of bullying and therefore fail to design proper solutions that guarantee students’ well-being. The results also show that these policies have started to notice the issue of inequality (considering factors such as race, gender) as a contributor to bullying, and while including it in their proposed solutions, the clarity and meaningfulness of its application have not been elaborated, explained, implemented, or researched enough. The main conclusion based on the findings of this research reveals that the current dominant construction of the bullying problem and its solutions remains narrowly focused on individual behaviors and psychological factors, overlooking the broader systemic and structural inequalities that contribute to its occurrence. Consequently, this limited framing restricts the effectiveness of anti-bullying policies and interventions, underscoring the urgent need for a more comprehensive approach that integrates social, cultural, and institutional dimensions to truly promote students' well-being and equity.
Keywords: Bullying, Anti-bullying policy, Foucauldian Discourse Analysis, Psychological Discourse, Neoliberal Discourse